Antioxidant and anti‐fatigue activities of egg white peptides prepared by pepsin digestion. (27th May 2014) - Sun, Shuguo; Niu, Huihui; Yang, Tao; Lin, Qinlu; Luo, Feijun; Ma, Meihu
Abstract BACKGROUND Some hydrolyzed peptides derived from food proteins possess antioxidant and anti‐fatigue activities. In this study, egg white protein powder (EWPP) was hydrolyzed with pepsin for various times, and four peptide fractions were separated from the hydrolysates by ultrafiltration. The antioxidant activity of the four peptide fractions was determined. The peptide fraction with the strongest antioxidant activity was used to evaluate its anti‐fatigue effect and probable mechanisms. RESULTS The egg white peptides (EWPs) fraction with molecular weight 2–5 kDa (named EWPs2) showed stronger antioxidant activity than the other peptide fractions (P < 0.05). The swimming time to exhaustion of mice administered EWPs2 was longer (P < 0.05) than that of the control group. EWPs2 increased the levels of blood glucose (by 28.4–42.2%), muscle glycogen (by 6.4–10.6%) and liver glycogen (by 10.7–23.8%) and significantly decreased the levels of lactic acid in muscle and urea nitrogen in blood (P < 0.05). CONCLUSION Among the four peptide fractions, EWPs2 possessed the strongest antioxidant activity and exhibited an anti‐fatigue effect. The experimental data could clarify partially the anti‐fatigue mechanisms of EWPs and provide an important basis for developing EWPs as safe and natural antioxidants and anti‐fatigue agents for wide use. © 2014 Society of Chemical Industry